Editors’ Introduction for NANO Special Issue 13: The Anthropocene - Kyle Wiggins and Brandon Krieg (New York City College of Technology, 2018)
What does it mean, then, to be human—even a human environmentalist—on a planet imperiled by our presence? That question underlies this special issue of NANO on the Anthropocene through three articles and two critical interviews.